Scotland + Venice 2013 : Sworn, Campbell, Tompkins. - Exhibition Venezia. Palazzo Pisani 2013-6,1 (Glasgow : The Common Guild, 2013)
A set of three 16-page booklets published to accompany an exhibition of three Scottish-based artists exhibiting at the 55th International Venice Biennale in the Palazzo Pisani from 1 June - 24 November 2013. The three small colour-illustrated works on lesser known artists - Duncan, Campbell, film maker, Hayley Tompkins, painter and Corin Sworn, installation artist - include biographical details of the artists as well as short essays on their work. Although all were born in England and Ireland, all three live and work now in Glasgow and are representing Scottish art at this event. For anyone unable to travel to Venice this year, their works will form part of the 'Generation: 25 years of contemporary art in Scotland' exhibitions being mounted as part of the 2014 Commonwealth Games being geld in Glasgow next year. Exhibition: Palazzo Pisani, Venice, Italy (01.06.-24.11.2013).
3. Corin Sworn
Exhibition 1 June-24 November 2013
boek